Roles of interleukin-17 in uveitis - Guedes, MC (2016)
Th17 cells, a CD4+ T-cell subset, produce interleukin (IL)-17, a pro-inflammatory cytokine that has been shown to be involved in several forms of infectious and noninfectious uveitis. Here, we explore the roles of this IL in uveitic disorders as well as in experimental autoimmune uveitis, the possible pathogenic implications of several cytokines associated with IL-17 and analyze the current outcomes and goals for drugs aiming for the IL-17 pathway.